Design, Synthesis, Antimicrobial, and Anticancer Activities of Acridine Thiosemicarbazides Derivatives - Rui Chen; Lini Huo; Yogini Jaiswal; Jiayong Huang; Zhenguo Zhong; Jing Zhong; Leonard Williams; Xing Xia; Yan Liang; Zhenshuo Yan (Molecules, 2019)
Background: Acridine and thiourea derivatives are important compounds in medicinal chemistry due to their diverse biological properties including anticancer and antimicrobial effects. However, literature reveals some side effects associated with use of acridines. It is suggested that hybrid molecules may reduce the side effects and enhance the beneficial properties due to synergistic activity. The objectives of the present study are to synthesize and evaluate the anticancer and antimicrobial properties of new hybrids of acridine thiosemicarbazides derivatives. Results: The structures of the synthesized compounds 4a−4e were elucidated by MS and NMR spectra. In antimicrobial assay, Compound 4c exhibited potent antimicrobial activity compared to the other four compounds. In anticancer studies, we observed that compounds 4a, 4b, 4d and 4e exhibited high cytotoxicity against the MT-4 cell line, with IC50 values of 18.42 ± 1.18, 15.73 ± 0.90, 10.96 ± 0.62 and 11.63 ± 0.11 μM, respectively. The evaluation of anticancer effects, and the associated mechanism reveals that, the anticancer activities may be related to Topo I inhibitory activity, apoptosis and cell-cycle. Molecular docking studies revealed that the presence of planar naphtho-fused rings and a flexible thiourea group together, could improve DNA-intercalation and inhibition of DNA-Topo I activity. Conclusions: The results of this study demonstrate that the rational design of target derivatives as novel antimicrobial or antitumor leads is feasible.